The Effectiveness of Physical Activities on Fatigue In The Elderly: A Systematic Review - Hendrik Prayitno Luawo; Tintin Sukartini; Joko Suwito (STRADA : Jurnal Ilmiah Kesehatan, 2020)
The method in preparing this Systematic review is based on literature studies from various electronic databases including Scopus, Proquest, CINAHL, MEDLINE, and ScienceDirect by conducting a comprehensive review using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyzes) guidelines. The keywords used are"effectiveness and "physical activity" AND "fatigue" AND "elderly". There are 9 original articles with 6 articles using the Randomized Control Trials (RCTs) research method, 2 articles using the quasi-experimental method, and 1 article using the prospective cohort method according to the inclusion criteria. This systematic review shows the effectiveness of various physical activities on reducing fatigue in the elderly, this systematic review can be used as evidence when doing a combination of joint activities and self-exercise at home as a good choice physical exercise intervention for the purpose of reducing fatigue in the elderly